Cross-cultural forensic reports of torture survivors based on the Istanbul Protocol - Pérez-Sales, Pau (Torture Journal, 2024)
The text provides an overview of the key considerations for conducting a cross-cultural assessment of a torture survivor. The first part provides an introduction to essential concepts in anthropology, medicine, and cross-cultural psychology and psychiatry. The second part reviews the most relevant elements in relation to a forensic report of a survivor, with a particular focus on cultural considerations regarding the ethical aspects of the Istanbul Protocol. It also addresses aspects related to the encounter with the survivor and the interview, medical aspects including the physical examination with a special focus on pain and suffering, the psychological and psychometric assessment. It also briefly discusses aspects related to consistency and credibility analysis. In the last section, the text provides an overview of cultural consideration following the outline of the Istanbul Protocol.